2019
DOI: 10.18502/jovr.v14i4.5457
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Learning Styles among Ophthalmology Residents: An Iranian Sample

Abstract: PurposeThis study was performed to assess the learning styles of a sample of Iranian residents through Kolb's and VARK questionnaires.MethodsIn this descriptive-analytical study, 45 ophthalmology residents of Mashhad University of Medical Sciences were enrolled. Kolb's and VARK questionnaires were provided, and residents were oriented and guided on how to complete them.ResultsForty-three out of the forty-five ophthalmology residents completed the questionnaire (95.5% response rate). The preferred learning styl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Interns were more likely to learn with the logic analysis method based on observation and conceptualization and lacked the skill to perceive information through concrete experience and processing information through active experimentation. The study results were consistent with Samira Hassanzadeh et al and Int J Health Sci (Qassim) et al [16][17][18][19], which found that the majority of undergraduate nursing students were assimilators, while few of them were accommodators. Yet, these data were inconsistent with Fatemeh et al [12,10] which foudings were the most dominant learning style of the nursing students was the divergent one, which may be related to traditional education in China, where students have clear learning objectives and like to think and analyze, but are not good at practice.…”
Section: Discussionsupporting
confidence: 91%
“…Interns were more likely to learn with the logic analysis method based on observation and conceptualization and lacked the skill to perceive information through concrete experience and processing information through active experimentation. The study results were consistent with Samira Hassanzadeh et al and Int J Health Sci (Qassim) et al [16][17][18][19], which found that the majority of undergraduate nursing students were assimilators, while few of them were accommodators. Yet, these data were inconsistent with Fatemeh et al [12,10] which foudings were the most dominant learning style of the nursing students was the divergent one, which may be related to traditional education in China, where students have clear learning objectives and like to think and analyze, but are not good at practice.…”
Section: Discussionsupporting
confidence: 91%
“…performance and skill, such as intraoperative c o m p l i c a t i o n s , 2 1 , 2 2 , 2 9 , 3 7 , 4 0 s u r g e r y performance, 22,[27][28][29]36 aesthetic grade, 42 surgery completion, 22 and surgical efficiency. 39,42 Several studies investigated learning outcomes, such as ex am in at io n p er fo r man ce, 2 4 , 3 1 , 4 3 lear n in g readiness, 35 learning style, 30 and learning barriers. 33 N i n e s t u d i e s e x a m i n e d c o m p o n e n t s o f validity.…”
Section: Table 2 Describes Outcomes and Study Results Most S T U D I ...mentioning
confidence: 99%
“…The most common study types were prospective cohort [21][22][23][24][25][26][27][28][29] and cross-sectional. [30][31][32][33][34][35][36] Studies were most commonly conducted in the United States, 27,[37][38][39][40][41][42] Denmark, 23,28,36,43 and the United Kingdom. 25,26,44,45 Only 7 studies 22,26,31,32,35,44,46 had sample sizes over 50 participants (range 52-311).…”
Section: Characteristics Of Included Studies and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In addition, students employ various sensory means to obtain and assimilate knowledge. 7 Fleming described four sensory modalities comprising visual (V), aural (A), reading/writing (R) kinesthetic (K) called as VARK. 8 In short, visual students learn better by seeing, aural students use listening methods, while some students study better by reading/writing and kinesthetic students use physical methods as a preferential technique to accommodate information.…”
Section: Introductionmentioning
confidence: 99%